Students’ Perception Towards Online Listening Class - Umiati Rui'yah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Keywords: perception, online learning, listening. Online learning has been adopted in education around the world due to social distancing to prevent Covid-19 from spreading. All teaching and learning activities online learning are done through internet connection. In terms of ELT context, creative and conducive learning method needs to be developed to cover learning need, Listening is considered to be very complex to be adjusted in online learning environments as the activities involves complex learning method that highly dependent on direct supervision of the instructor. Suitable is needed to be developed in designing learning environment. Therefore, the researcher aims to conduct study about students’ perception in online listening.This study used descriptive qualitative research method and semi structured interview as instrument. The data for this research collected from 10 students of English department from University of Islam Malang through online with the use of WhatApp video call. The data are analysed using qualitative data analysis based on Miles and Huberman (1994) that consist of data reduction, grouping, coding, and interpretation to get the data as a whole.The result identifies that online learning activities in listening class focuses on revealing the learner with authentic material and encourages students to practice listening skill independently especially IELTS by providing the students with suitable and sufficient material. It also found that learning platform are applied effectively. The study also identifies that the participants have positive responses towards online listening such as enjoyable, practical and flexible, well delivered and facilitated, good instructor and more successful compared to previous semester.